Analisis Perilaku Balok Beton Bertulang dengan Perkuatan Fiber Reinforced Polymer (FRP) Berdasarkan Variasi Tinggi - Silvi, Ni Putu; Laintarawan, I Putu (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2025)
Structural failure due to structural design that does not meet the minimum standards according to SNI results in structural failure, one of which is cracks. One of the popular strengthening for reinforced concrete beams is using FRP (Fiber Reinforced Polymer). This is because FRP has the advantages of being lightweight, easy to install, corrosion resistant and does not interfere with the function of the structure. The purpose of this study was to determine the behavior of strengthening reinforced concrete beam structures using FRP with variations in FRP strengthening height against reinforced concrete beams without strengthening. The method used in this study is a quantitative method using FRP height variation data which is modeled and analyzed using the finite element method. Modeling and analysis using SAP2000 software assistance with 5 (five) models, namely model 1 is a model without reinforcement, models 2, 3, 4 and 5 with FRP heights of 0.25h, 0.5h, 0.75h and h respectively. The FRP thickness is 5 mm. The loads calculated in the analysis are the ultimate dead and live loads according to SNI 1727: 2020 (SNI Loading) and SNI 2847: 2019 (SNI Concrete). Based on the analysis results, strengthening reinforced concrete beams with FRP can reduce vertical deflection due to the ultimate load by an average of 46.146% compared to beams without strengthening. The ultimate moment of the support and the field of the FRP-strengthened beam can increase the ultimate flexural and shear capacity by an average of 0.242% compared to beams without strengthening. Likewise, the bending stress s11 min and s11 max of the FRP-strengthened beam can increase the average bending stress capacity by 21.65% compared to beams without strengthening. The maximum stress and strain contours decrease as the FRP strengthening height increases.